Translation Equivalence in the Song ‘Satu Bulan’ by Bernadya with the Arabic Version - Mukminin, Muhamad Saiful; Sitorismi, Aninda Ayu (Lughaat: Journal of Arabic Linguistics, 2025)
This study examines the translation equivalence in the song Satu Bulan by Bernadya and its Arabic version Syahr Ba'd. Using a qualitative descriptive approach, this research aims to explore how meaning, structure, and cultural nuances are preserved or altered during translation. The data consists of the Indonesian lyrics of Satu Bulan and its Arabic translation. Data collection is conducted through a documentation of the two texts, focusing on key phrases, idiomatic expressions, and cultural elements. The analysis employs interactive model, encompassing data reduction, data display, and conclusion drawing. Findings reveal that most translations achieve equivalence, particularly at word, above the word, grammatical, and pragmatic levels. The translator effectively maintains word meanings and adapts sentence structures and grammatical categories to suit the target language. However, some non-equivalent translations were identified, involving shifts in meaning or loss of nuance. These imbalances are primarily influenced by cultural differences, idiomatic expressions, and structural variations between Indonesian and Arabic. Overall, the translation successfully balances linguistic accuracy and cultural adaptation, with minor deviations that reflect the complexities of cross-language equivalence.